Petrarch – the first modern poet - Kostić, Tatjana T. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Francesco Petrarch is the father of the Italian literature and was on the forefront of the humanists who influenced the formation of a new age culture. He lived in the time of mixing discourse: a Christian religion and Humanistic philosophy. He wrote in Italian and Latin. He reached affirmation with Canzoniere, collection written in a common folk language. Without Petrarch’s work in Latin, it’s impossible to perceive neither Canzoniere, nor the spirit of the time which reflects the poetry of Petrarch. Canzoniere doesn’t narrate only about love for Laura, but expresses a complex, far-reaching message that collects ideological and moral crisis of the new century which makes Petrarch the first modern poet. Popularity of Petrarch’s poetry spread throughout Europe and created a phenomenon called Petrarchism. Afterwards, Petrarch’s influence is evident in the Romantic and Modern literature (Modern and Postmodern). Petrarch was the first modern poet, because he opened the subject of the relationship between a man and God. Petrarch’s poetry is not only individual experience of the poet, but the universal experience of the New Age man who is experiencing existential problems and therefore Canzoniere excites the human spirit even today. Petrarch presented the intimate lyrical experience of a man searching for meaning, a man only aware of his finality. This became a constant that characterizes modern literature in various periods of literary history.